GANGGUAN MOOD PADA STROKE - Tantular, Gabriella; Westa, Wayan; Nuartha, AABN (Medicina; Vol 46 No 1 (2015): Januari 2015, 2015)
Stroke adalah salah satu sindrom neurologi yang dapat menimbulkan kecacatan dalam kehidupanmanusia. Salah  satu gejala yang dapat  timbul  setelah  seseorang  terkena  stroke adalah gangguanmood. Gangguan mood berhubungan dengan disabilitas fisik, beratnya stroke dan gangguan kognitif.Gangguan mood yang ditemukan pada stroke adalah depresi, gangguan afektif bipolar dan mania.Gambaran  gejala  berhubungan dengan  lesi  anatomis  stroke. Terapi  yang diberikan dapat  berupafarmakologis, psikoterapi, dan rehabilitasi. [MEDICINA 2015;46:33-36]. Stroke is one of neurology syndrome that cause disability in human life. One of the symptoms thatappear after stroke was mood disorder. Mood disorder were related to physical disability, severity ofstroke  and  cognitive  dysfunction. Mood  disorder  found  in  stroke was  depression,  affective  bipolardisorder, and mania. Symptoms were associated with anatomical lesion. Treatment for this disorderare pharmacologic treatment, psychotherapy, and rehabilitation. [MEDICINA 2015;46:33-36].
Keywords: stroke, depression, affective bipolar disorder, mania